Canthaxanthin protects human sperm parameters during cryopreservation. (11th August 2019) - Najafi, Leila; Halvaei, Iman; Movahedin, Mansoureh
Abstract: Different antioxidants have been introduced to reduce oxidative stress during the cryopreservation. The main goal of this study was to evaluate the effects of canthaxanthin on human sperm parameters during the freeze‐thaw process. This study was performed on 25 normozoospermic semen samples dividing into five groups including 0, 0.1, 1, 10, and 25 µM of canthaxanthin. The prepared spermatozoa were cryopreserved by rapid freezing technique. Sperm motility, viability (eosin‐nigrosin), morphology (Papanicolaou), acrosome reaction (double staining), DNA denaturation (acridine orange), chromatin packaging (aniline blue and toluidine blue), and DNA fragmentation (sperm chromatin dispersion test) were evaluated before freezing and after thawing. All sperm parameters after thawing significantly were decreased compared to before freezing. Twenty‐five micromolar canthaxanthin could significantly improve the progressive and total motility, viability, normal morphology, chromatin packaging, acrosome integrity and DNA denaturation and fragmentation. Ten micromolar canthaxanthin significantly improved total motility, viability, normal morphology, chromatin packaging, acrosome integrity and DNA denaturation and fragmentation. Whereas, in 1 µM group, there were significant differences only in improvement of acrosome integrity, chromatin packaging (toluidine blue) and DNA denaturation and fragmentation. But, in 0.1 µM group, there were no significant differences in any of measured parameters. It seems that canthaxanthin ameliorates detrimental effects of cryopreservation on human sperm parameters.